Challenges of Remote education in light of the Covid-19 pandemic: government secondary schools in Khartoum state as an exemplar - Mohammed Ali, Eman (Al-Adab Journal, 2024)
The study dealt with the challenges that faced education in government secondary schools in Khartoum State in light of the Corona pandemic, the study aimed to identify the most important of these challenges; the importance of this study comes to address an important segment of society, namely students. Because of the importance of education in society to produce generations with scientific thought based on transparency and social responsibility, this study may benefit decision-makers by providing the necessary needs for use and develop of distance education programs held by the Ministry of Education. The research relied on the analytical descriptive approach, as well as on studies and research published in the field of e-learning. The results of the study are the weakness in the use of technological skills for the teacher and the student in distance education, the weakness of the Internet in homes and power outages in many times, and the lack of computers for students by the Ministry of Education. The educational environment is not qualified to provide this electronic service, and the lack of most educational and academic institutions in employing modern technology within their educational plans. The researcher came out with several recommendations, the most important of which is the need to open a wide field for training teachers and students to use distance education platforms, improving internet and electricity services, strengthening the infrastructure in government schools in Khartoum State, Reviewing school curricula in order to comply with the requirements of distance education, the need for government agencies responsible for education to focus on providing equipment and tools for all students to ensure that students are not deprived of their basic right to education.